The Oxford handbook of Epicurus and Epicureanism - Mitsis, Phillip (Oxford University Press, 2020)
The ancient Greek philosopher Epicurus (340-271 BCE), though often despised for his materialism, hedonism, and denial of the immortality of the soul, has at the same time been an ongoing source of inspiration for a great variety of subsequent philosophers, poets, and political thinkers. This volume offers authoritative discussions of all aspects of Epicurus's philosophy and then traces out some of its most important later influences throughout the Western intellectual tradition. Epicurean arguments are carefully placed in their ancient and subsequent intellectual contexts, thus offering readers the opportunity of measuring them against a wide range of opponents - from Platonists, Aristotelians, and Stoics, to Hegel and Nietzsche, and finally on to such influential contemporary philosophers as Thomas Nagel, Bernard Williams, and Jacques Derrida.
Keywords: Epicurus; Aufsatzsammlung; Epikureismus